2016
DOI: 10.1016/j.bbmt.2015.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Indications and Results of HLA-Identical Sibling Hematopoietic Cell Transplantation for Sickle Cell Disease

Abstract: Although there are a number of published trials of human leukocyte antigen (HLA) – identical sibling hematopoietic cell transplantation (HCT) for sickle cell disease (SCD) that span 2 decades, when and for whom this therapy should be pursued is a subject of debate. Assessments of the risks of transplant-related complications that include infertility and debilitating graft-versus-host disease and long-term quality of life after successful HCT are difficult to perform without prospective trials in transplant and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 106 publications
(72 citation statements)
references
References 44 publications
1
70
0
1
Order By: Relevance
“…38 Consensus reports on indications for transplantation may increase awareness, with early referral for accepted indications. 17,39 Others have reported the observation that HLA-matched sibling transplantation performed in view of abnormal transcranial Doppler velocities allowed for discontinuation of transfusions in all patients. 12 Although survival in children has improved substantially over the years, the median survival of adults is about 20 years shorter than in the general population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…38 Consensus reports on indications for transplantation may increase awareness, with early referral for accepted indications. 17,39 Others have reported the observation that HLA-matched sibling transplantation performed in view of abnormal transcranial Doppler velocities allowed for discontinuation of transfusions in all patients. 12 Although survival in children has improved substantially over the years, the median survival of adults is about 20 years shorter than in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…11 Although several reports have demonstrated that HLA-identical sibling transplantation with bone marrow (BM) or umbilical cord blood (CB) establishes normal hematopoiesis and is associated with excellent survival, most studies were conducted at single institutions or in the context of clinical trials. [12][13][14][15][16][17] The current study sought to describe outcomes after HLA-identical sibling transplantation for SCD worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Crucially, ,1 in 10 of these families will have to cope with the major adverse outcome of BMT transplant-related mortality (TRM) and severe chronic graftversus-host disease (GVHD). 2,3 Given that SCD causes premature death and disability, particularly in young adults, and has a major impact on the quality of life for patients at all ages and their families, 4 these are convincing results. Can similarly impressive results be achieved for the 80% to 90% of patients with SCD who do not have HLA-matched family donors?…”
Section: Imperial College Healthcarementioning
confidence: 73%
“…2,3 Overall, the outcome is extremely good, and BMT remains the best immediate prospect for long-term cure for children who are currently experiencing severe sickle-related complications. 2,3 Compared with other disease-modifying therapies, such as regular transfusion and hydroxycarbamide, matched related donor BMT will not only stop ongoing vaso-occlusive crises and arrest progressive organ damage in most cases, but may also lead to regression of damage in some cases. 3 Aggregate results from case series and clinical trials show disease-free survival of ;92% and overall survival (OS) of ;95% of children and young adults with SCD with a matched sibling donor.…”
Section: Imperial College Healthcarementioning
confidence: 99%
See 1 more Smart Citation